Fake accounts, real activism: Political faking and user-generated satire as activist intervention. (June 2018) - Ferrari, Elisabetta
In this article, I explore user-generated political satire in Italy by focusing on fake political accounts. By fake accounts, I refer to humorous social media accounts that satirize a politician or a political organization through impersonation. I investigate political faking and user-generated satire as an activist intervention. Through in-depth interviews, I explore the motivations and the relationship with Italian politics of a sample of fake account creators. The results show that most of the satirists interviewed here consider satire as a form of activism and even those who do not, still recognize the subversive nature of satire. Furthermore, a majority of the interviewees have complex biographies of activism that predate the creation of the fake accounts. For a smaller number of them, the fake accounts have also provided new possibilities to engage in activism away-from-keyboard (AFK).